Determinants of high vaccine confidence and uptake among the Australian public: insights from a cross-sectional study - Williams, Charles Travers; Saini, Bandana; Zaidi, Syed Tabish R.; Castelino, Ronald L. (Frontiers in Public Health, 2025)
BackgroundIn 2021, Australia launched a national COVID-19 vaccine rollout strategy, but encountered setbacks that resulted in negative press and media controversy. This study aimed to confirm factors influencing vaccine confidence and uptake in Australian adults and validate the use of a Vaccine Confidence Scale.MethodsA cross-sectional study was conducted from 15 to 21 September 2021, coinciding with the expansion of COVID-19 BNT162b2 vaccine eligibility to all adults in Australia. A voluntary online survey assessed vaccine confidence and influencing factors among adults (≥18 years of age). Multivariate logistic regression was used to identify predictors of high vaccination confidence (score >30) and uptake using odds ratios (OR) with 95% confidence intervals to measure effect size.ResultsAmong 471 respondents, vaccine confidence (mean score 20/40) and uptake (29.7%) was low. Those who used government websites (OR 6.35; p < 0.001) and general practitioners (OR 4.05; p < 0.001), as sources of COVID-19 information, or had received a healthcare professional recommendation (OR 2.82; p < 0.01) were up to six times more likely to have high vaccine confidence, and were more likely to receive a vaccination. In contrast, the use of non-mainstream media and online sources decreased confidence and reduced the likelihood of vaccination by 60% (OR 0.37; p < 0.05). The Vaccine Confidence Scale demonstrated potential as a tool for rapidly assessing vaccine confidence and predicting the likelihood of vaccine uptake.ConclusionGreater emphasis should be placed on raising awareness of trusted sources for vaccine information, and immunization programs should consider incorporating vaccine confidence tools to enhance communication strategies and encourage vaccine uptake.